Business opportunities in the tourism industry in Israel and Egypt. - Gay, Choon Lin. (2008)
Tourism is an important component of the Egyptian and Israeli economies. This is hardly surprising as both countries have a multitude of tourist spots to attract the businessmen, pilgrims, leisure-seekers, scholars, those in search of health therapies and eco-tourists to visit the countries. Both the Egyptian and Israeli Governments are, however, not resting on their laurels as they face stiff competition from other tourist attractions for the tourist dollars. Both economies are actively taking steps to ensure that their respective tourism industries continue to be a major foreign exchange earner for their countries in the years ahead.